The Effect of the Cobra Stretch Training Method on Students' Kayang Abilities - Yoga Aziz Kurnia Anggara; Nurman Ramadhan; Mohamad Da'i (Gladi : Jurnal Ilmu Keolahragaan, 2026)
The bridge (kayang) is a fundamental floor gymnastics skill that requires spinal flexibility, back muscle strength, and abdominal muscle strength. However, many elementary school students experience difficulty performing the bridge due to limited flexibility and insufficient core muscle strength. Therefore, a specific stretching method is needed to improve this ability. This study aimed to examine the effect of the cobra stretch training method on students’ bridge ability. This research used a quantitative approach with a one-group pretest–posttest pre-experimental design to evaluate skill improvement after a structured intervention. The participants were 20 fifth-grade students of Dahor State Elementary School selected using total sampling. The intervention was conducted for four weeks, three times per week. The instrument was a validated performance observation rubric assessing starting position, back arch, position stability, and final position. Data were analyzed using descriptive statistics, Shapiro–Wilk normality test, paired sample t-test, and Cohen’s d effect size analysis. The results showed a significant improvement after the intervention (t = −17.172, p < 0.05), with the mean score increasing from 7.15 to 12.45. The effect size was very large (Cohen’s d = 3.84), indicating a substantial practical impact. It can be concluded that the cobra stretch method is effective and practical for improving students’ bridge ability and can be applied in Physical Education learning at the elementary school level